2020
DOI: 10.18632/aging.103191
|View full text |Cite
|
Sign up to set email alerts
|

STAT1-induced upregulation of lncRNA KTN1-AS1 predicts poor prognosis and facilitates non-small cell lung cancer progression via miR-23b/DEPDC1 axis

Abstract: Several of the thousands of long noncoding RNAs (lncRNAs) have been functionally characterized in various tumors. In this study, we aimed to explore the function and possible molecular mechanism of lncRNA KTN1 antisense RNA 1 (KTN1-AS1) involved in non-small cell lung cancer (NSCLC). We identified a novel NSCLC-related lncRNA, KTN1 antisense RNA 1 (KTN1-AS1) which was demonstrated to be distinctly highly expressed in NSCLC. KTN1-AS1 upregulation was induced by STAT1. Clinical study also suggested that higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…This lncRNA is first reported as differentially expressed in colorectal cancer cells and tissues (8). KTN1-AS1 is then reported to be upregulated in head and neck squamous cell carcinoma, hepatocellular carcinoma, and non-small cell lung cancer, and positively associated with tumorigenesis and unfavorable clinical outcomes (9)(10)(11)(12). Of note, most of these studies have reported that KTN1-AS1 acts as a competing endogenous RNA (ceRNA), competitively combining with miRNA response elements (MREs) to regulate downstream protein-coding gene expression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lncRNA is first reported as differentially expressed in colorectal cancer cells and tissues (8). KTN1-AS1 is then reported to be upregulated in head and neck squamous cell carcinoma, hepatocellular carcinoma, and non-small cell lung cancer, and positively associated with tumorigenesis and unfavorable clinical outcomes (9)(10)(11)(12). Of note, most of these studies have reported that KTN1-AS1 acts as a competing endogenous RNA (ceRNA), competitively combining with miRNA response elements (MREs) to regulate downstream protein-coding gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions between KTN1-AS1, miRNAs, and mRNAs generate complex regulatory axes and are involved in the regulation of cancer cell behavior (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the significantly individual variation, a class of genetic markers including coding and non-coding genes attracted increasing attentions in the past few years [ 24 – 26 ]. Liu et al indicated lncRNA KTN1-AS1 played the remarkable roles on predicting the poor prognosis of non-small cell lung cancer and facilitate tumor progression through regulating miR-23b/DEPDC1 axis [ 27 ]. Zhou et al developed a profile of TILBlncSig consisting of eight long non-coding RNAs (lncRNAs) identified from 141 B cell specific lncRNAs and demonstrated the potential implications in prognosis of bladder cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA Kinectin 1-Antisense RNA 1 (KTN1-AS1) is located on chromosome 14 and was demonstrated to be upregulated in non-small cell lung cancer, hepatocellular carcinoma and head and neck squamous cell carcinoma, where it was confirmed to act as an independent prognostic factor ( 21 – 24 ). Previous studies reported that KTN1-AS1 promotes the development of hepatocellular carcinoma and non-small cell lung cancer ( 21 , 22 ). Jiang et al ( 23 ) also demonstrated that KTN1-AS1 can suppress the epithelial-mesenchymal transition in head and neck squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%